#TITLE_ALTERNATIVE# - Wahyudi (NIM 20595017), Mariana
ABSTRACT: Protein disulphide isomerase (PDI) is a multi-enzyme involved in catalyzing redox and isomerization reactions of disulphide bonds in secretory proteins. Disulphide bonds are necessary and very important in constructing the conformation of native protein. PDI was found in various living organisms and have been isolated from fungi, plants, mammals, etc. This investigation is focused on the isolation and partially purification of PDI from Saccharomyces cerevisiae (pUKC470) to elucidate mechanism of action of PDI by characterizing kinetics of the enzyme. The specific activity of PDI isolated from transformant increased by 17 fold compared to the wild type Saccharomyces cerevisiae W303. The purification of PDI from transformant using ammonium sulphate fractionation followed by ion exchange chromatography on DEAE-Sephacel revealed that the specific activity of PDI increased to 255.28 unit per mg, a degree of purity 137 fold compared to the cells free extract, and yield of 41 %. The partially purified enzyme has optimum time of 13 minutes, optimum pH of 7.5 and optimum temperature of 37 degree C. Kinetics data indicated that PDI is an allosteric enzyme which positive cooperatively interact to the substrate showed by the positive value of Hill constant (h) of 3.4, the upper limit of h which is equal to 4 indicated that the enzyme has 4 binding sites for its substrate. Furthermore, PDI has V. of 98 unit per mL and apparent KM of 8.0 x 10 2 mM. Bacitracin inhibited PDI by increasing the apparent KM but maintaining the V constant, hence it was concluded that PDI belongs to the K type allosteric enzyme.